Pengaruh Penggunaan Media E-learning Berbantuan Quizizz terhadap Hasil Belajar Siswa SMA Negeri 16 Semarang - Wibawanti, Diah; Benardi, Andi Irwan (Edu Geography, 2021)
This study aims to analyze the use of e-learning media assisted by quizizz class XI IPS SMA Negeri 16 Semarang City and determine whether there is an effect of the use of media quizizz on the learning outcomes of class XI IPS SMA Negeri 16 Semarang City. Researchers collected data using questionnaires and test instruments. The data analysis technique used percentage descriptive analysis and the analysis used the t test. The results showed that the variable use of media was 84.68% which indicated that the use of e-learning media assisted by quizizz was classified (81% -100%) which showed a very high category. The variable learning outcomes t count on the test using the paired sample t-test sig (2 tailed) <0.05 indicates that if there is an influence on the post-test results of the experimental class using quizizz, the result is 81.72 while in the control class post-test the mean value - The average is 68 so that there is a significant effect. The conclusion of this study is "there is a significant effect of using e-learning media with quizizz-assisted on the learning outcomes of class XI IPS SMA Negeri 16 Semarang in 2020/2021" Penelitian ini bertujuan untuk menganalisis penggunaan media e-learning berbantuan quizizz kelas XI IPS SMA Negeri 16 Kota Semarang dan mengetahui ada tidaknya pengaruh penggunaan media quizizz terhadap hasil belajar kelas XI IPS SMA Negeri 16 Kota Semarang. Peneliti mengumpulkan data menggunakan angket dan instrumen tes. Teknik analisis data menggunakan analisis deskriptif persentase dan analisis menggunakan uji t. Hasil penelitian menunjukkan variabel penggunaan media 84,68% yang menunjukan bahwa penggunaan media e-learning berbantuan quizizz tergolong (81% - 100%) yang menunjukan kategori sangat tinggi. Variabel hasil belajar angka t hitung pada pengujian menggunakan uji paired sampel t- test sig (2 tailed) < 0,05 menunjukan jika terdapat pengaruh pada hasil post-test kelas eksperimen menggunakan quizizz hasilnya adalah81,72 sedangkan pada post-test kelas kontrol nilai rata- rata yaitu 68 sehingga terdapat pengaruh yang signifikan. Simpulan dari penelitian ini adalah â€œada pengaruh signifikan penggunaan media e-learning berbantuan quizizz terhadap hasil belajar kelas XI IPS SMA Negeri 16 Semarang tahun 2020/2021â€.